2022
DOI: 10.1186/s40748-022-00144-y
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasive sensor methods used in monitoring newborn babies after birth, a clinical perspective

Abstract: Background Reducing the global new-born mortality is a paramount challenge for humanity. There are approximately 786,323 live births in the UK each year according to the office for National Statistics; around 10% of these newborn infants require assistance during this transition after birth. Each year around, globally around 2.5 million newborns die within their first month. The main causes are complications due to prematurity and during delivery. To act in a timely manner and prevent further d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 71 publications
0
3
0
Order By: Relevance
“…Research by Ramanathan et al has also shown the effectiveness of the technical properties and how the limitations of stethoscope technology could affect potential uses in the fields of pediatrics and neonatology, from telemedicine to computer-aided diagnostics [64]. Studies were also performed to provide non-invasive methods to monitor the heart rate and respiratory rate in neonates [65] and to assist in bedside monitoring and the diagnosis of pediatric and cardiology patients [66].…”
Section: Feature-based Benchmarkingmentioning
confidence: 99%
“…Research by Ramanathan et al has also shown the effectiveness of the technical properties and how the limitations of stethoscope technology could affect potential uses in the fields of pediatrics and neonatology, from telemedicine to computer-aided diagnostics [64]. Studies were also performed to provide non-invasive methods to monitor the heart rate and respiratory rate in neonates [65] and to assist in bedside monitoring and the diagnosis of pediatric and cardiology patients [66].…”
Section: Feature-based Benchmarkingmentioning
confidence: 99%
“…An example of its importance is the prevention of sudden cardiac arrest in newborns with long QT syndrome (Saul et al, 2014;Brockmeier, Nazal, and Sreeram, 2016). Multiple technologies are being developed for newborn remote long-term monitoring applications utilizing ECG and other vital signs such as respiratory activity and temperature (Aviles-Espinosa et al, 2019;Fraiwan et al, 2009;Taylor et al, 2022;Lin et al, 2019;Anton et al, 2022;Henry et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, automating the measurement and recording of vital signs can help reduce the workload of nursing staff [19]. Inter-rater reliability issues of contact sensors can be improved through repetitive monitoring with a single device and can significantly lower the risk of skin-related problems because there is no contact between the devices and the skin [20]. This article reviews the medical use of noncontact sensors for measuring vital signs and aimed to determine their potential clinical applicability.…”
Section: Introductionmentioning
confidence: 99%